Erratum - Editorial
A blind caries and fluorosis prevalence study of school-children in naturally fluoridated and nonfluoridated townships of Morayshire, Scotland Kenneth W. Stephen, Lorna M. D. Macpherson, W. Harper Gilmour, Russell A. M. Stuart andMartyn C. W. Merrett